2017
DOI: 10.1111/jfcj.12092
|View full text |Cite
|
Sign up to set email alerts
|

Race and Gender Recidivism Differences Among Juvenile Mental Health Court Graduates

Abstract: Grounded in the theory of therapeutic jurisprudence, this research explores whether recidivism differs by race, ethnicity, or gender among juvenile mental health court graduates (N = 63). Mean number of pre‐program offenses were compared to the mean number of offenses committed by program completion. Results showed statistically significant reductions in recidivism by both males (p < .001) and females (p < .003). Racial and ethnic minorities demonstrated larger reductions when compared to Whites (p < .001 for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…The National Council of Juvenile and Family Court Judges (NCJFCJ) outlines a trauma‐informed court as a system where communities and policies are created to diminish trauma‐induced stress responses of those with a history of trauma (NCJFCJ, 2015; Simons et al, 2002). Interestingly, racial and ethnic minorities are disproportionately represented within the juvenile justice system yet have a decreased likelihood of being chosen for alternative adjudication when compared to their White counterparts (Behnken et al, 2017; Rodriguez, 2005). Thus, juveniles of color have fewer opportunities to obtain treatment.…”
Section: Racial Battle Fatigue In Adolescencementioning
confidence: 99%
“…The National Council of Juvenile and Family Court Judges (NCJFCJ) outlines a trauma‐informed court as a system where communities and policies are created to diminish trauma‐induced stress responses of those with a history of trauma (NCJFCJ, 2015; Simons et al, 2002). Interestingly, racial and ethnic minorities are disproportionately represented within the juvenile justice system yet have a decreased likelihood of being chosen for alternative adjudication when compared to their White counterparts (Behnken et al, 2017; Rodriguez, 2005). Thus, juveniles of color have fewer opportunities to obtain treatment.…”
Section: Racial Battle Fatigue In Adolescencementioning
confidence: 99%
“…In addition, the authors found that mental health issues were indirectly related to offending, highlighting the need to consider other criminogenic needs during programming (Davis et al, 2015). Regarding differences in JMHC outcomes by race and gender, one study found that participation decreased the likelihood of recidivism for both boys and girls and that racial and ethnic minorities had significantly larger reductions than white participants (Behnken et al, 2017). While research on the effectiveness of JMHCs is largely positive across various demographic groups and geographical locations, research has yet to examine the prevalence and of trauma in this population.…”
Section: Introductionmentioning
confidence: 99%
“…Given that history of childhood, sexual abuse trauma is one of the strongest predictors for female juvenile recidivism, gender-specific interventions should also be tailored to address the trauma-exposed population [ 38 ]. Emerging research efforts suggest that programming with gender-responsive features is associated with a lower risk of recidivism for girls who present with gender-specific risk factors (e.g., trauma) [ 2 ].…”
Section: Introductionmentioning
confidence: 99%